(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2012)
Paper presents the study of the determination of the energy of impact on wooden specimens of Eucalyptus gomphocephala, Moroccan species of good mechanical characteristics but deemed by his nervousness, which harms its use as timber. In many cases, wood is exposed to undergo temporary and abrupt efforts, shocks, vibrations (pit props, crash barriers, bridges and footbridges….). For some species of Eucalyptus, an abnormal withdrawal may involve a localized failing-in of wood cells which produces an apparent deformation or collapse. During our study, we determined the energy absorbed by notched or unnoched specimens, well defined subjected to the impact test of Charpy, under different states of moisture at controlled temperature, consequently various variations of volumetric withdrawal have been observed.